Preliminary Characterization of Root Nodule Bacteria from Viglla acollitifolia - Chakraborty, Manigopa; Ramkrishna, K (Annals of Arid Zone, 2016)
Indigenous rhizobia nodulating Viglla acollirijiJ!ia from three agroclimatically different zones of semi-arid region of Rajasthan state of India IVere investigated. The rhizobia consisting of 146 isolates were characterized on the basis of intrinsic resistance to different antibiotics, UV arid azide and colony properties. Fifty three per cent of the isolates produced waxy mucilage. The isolates represcnting most arid region were both antibiotic and UV sensitive whereas those from least arid zone were relatively tolerant to both of these. Of these rhizobia, two isolates which showed pink and big nodules on the host plants, MR 125s2 was not only antibiotic and UV sensitive but also susceptible to phage. These two isolates also produced waxy mucilage. It is inferred that waxy mucilage and susceptibility to both biotic and abiotic factors may confer the bacteria an increased adaptedness to both plant and soil.